The cultural significance of the rural Great Plains county seat: a case study of two western Kansas counties - McAlister, Jordan (Kansas State University, 2014)
The county seat town holds an important role in American geography. Whether serving simply as a governmental or judicial meeting place for a specific political district, or acting as an economic hub for a county and its surrounding hinterlands, any given American county seat exists with a variety of different cultural meanings imposed upon it. This study analyzes the historical and cultural geographies of two rural counties in the heart of the American Great Plains which have, or at one time had, exceptionally small county seats of fewer than 250 residents. Both counties are adjacent to one another in western Kansas. One, Logan County, originally had its county seat located near its geographic center in the village of Russell Springs, but relocated its seat in the 1960s to the larger town of Oakley. Gove County, today maintains its original county seat of roughly 150 inhabitants near its geographic center despite the presence of more populated towns within the county’s boundaries. Both counties provide excellent material for a case study devoted to understanding what the role of the county seat is in rural America today. In this study I find that the discrepancies between these counties and their seats arise from the different ways in which distinct cultural groups understand or interact with the county seat. An individual’s age, ethnicity, land use or livelihood practices, and location within a county all have an effect on their interpretation of the role of the county seat. This thesis provides a glimpse into the complex cultural nature of rural Great Plains communities through the lens of historical and geographical change.
Keywords: County seats; Western Kansas; Great Plains; Rural; Perceptions; Geography; Geography (0366)